Chemical composition, antioxidant capacity and phenolic contents of carob (Ceratonia siliqua L.) flour as related to seed presence and roasting effects - Brassesco, María (2022)
Carob is the fruit of an evergreen tree (Ceratonia siliqua L.) cultivated in the Mediterranean area, where Portugal has a high-cultivated extent with relevant production and low prices. Carob is well known for its valuable locust bean gum. However, carob pods contain various relevant nutrients, including proteins, carbohydrates and fiber, and phytochemicals such as polyphenols, which position carob flour with great potential to be used as a functional ingredient. This study aimed to evaluate the impact of different roasting processes of carob flour (with and without seeds) on its nutritional composition and antioxidant activity. Seed presence led to a higher content of macronutrients in carob flour. The roasting processing affected the total content of polyphenols (TPC), determined by Folin-Ciocalteau, since the content at 150 ºC was twice of that obtained at 80 ºC, probably due to the formation of certain Maillard reaction products (MRPs), or certain phenolics that may degrade during roasting. The antioxidant activity is correlated with TPC, increasing when the flour was roasting at 150ºC. Regarding the total fiber content, a significant increase was observed in samples processed at 150 ºC. These findings confirm the importance of understanding the impact of processing on the nutritional value and bioactive properties of carob flours, to use them efficiently as a functional food ingredient.